Perspectivas y expectativas de los padres de familia en los CIBV del cantón Otavalo - Romo Jacho, Fernanda Elizabeth (2018)
The purpose of this degree work is to investigate the perspectives and expectations of parents of children about CIBV in the canton of Otavalo, for these six theses prepared by the students of the professional career were analyzed of Intercultural Bilingual Education. The problem that is exposed in the work is that there is no correct processing of the information collected, so it is decided to systematize the files containing the new data collected and unified from the survey that was carried out in 163 parents. In addition, within the systematization are key terms that can help to better understand the subject, for this basic concepts are presented, early childhood, authors of the activist and constructivist approaches, the function of the CIBV and the culmination with information from the canton Otavalo, this information is important because based on this, a contrast is made with the results obtained in order to conclude this investigative work.